Marketing Strategy Through Distribution, SWOT Analysis and Promotional Media to Increase Sales of Jelita Food Fruit Salad - Aslami, Nuri; Jelita, Nadila; Tanjung, Nur Azizah (Taqaddum: Community Service Journal, 2023)
The purpose of this study is to find out marketing strategies through distribution, SWOT analysis and promotional media in order to increase sales of Jelita Food Fruit Salad, with the research method used, namely a situational approach, then all data is analyzed to obtain good and relevant research results. Based on data from interviews with the owner of Jelita Food and sales analysis, Marketing Strategy Through Distribution, SWOT Analysis and Promotional Media to Increase Sales of Jelita Food Fruit Salat, can increase sales as shown in the sales table for the last three months at Jelita Food Fruit Salat. Where sales turnover in October was IDR 950,000 for 95 cups, in November IDR 1000,000 for 100 cups, and in December IDR 1,050,000 for 105 cups. The fast-responsive fruit salad food business carries out a strategy to evaluate its sales, by marketing through distribution with open resellers, distributing brochures, participating in bazaars, expos, updating trends and adapting them to the marketing of its business.